Advances in genetic manipulation of Chlamydia trachomatis - Wan, Weiqiang; Li, Danni; Li, Dan; Jiao, Jun (Frontiers in Immunology, 2023)
Chlamydia trachomatis, one species of Chlamydia spp., has the greatest impact on human health and is the main cause of bacterial sexually transmitted diseases and preventable blindness among all Chamydia spp. species. The obligate intracellular parasitism and unique biphasic developmental cycle of C. trachomatis are the main barriers for the development of tools of genetic manipulation. The past decade has witnessed significant gains in genetic manipulation of C. trachomatis, including chemical mutagenesis, group II intron-based targeted gene knockout, fluorescence-reported allelic exchange mutagenesis (FRAEM), CRISPR interference (CRISPRi) and the recently developed transposon mutagenesis. In this review, we discuss the current status of genetic manipulations of C. trachomatis and highlights new challenges in the nascent field of Chlamydia genetics.